Binary PSO algorithm assisted to investigate the optical sensor based plasmonic nano-bi-domes - Keshavarzi, Rasul; Akhlaghi, Majid; Emami, Farzin (Optik (Stuttgart), 2016)
In this paper, a coherent perfect absorption (CPA)-type sensor based on plasmonic nano particle is proposed. It consists of a plasmonic nano bi-domes array on top of a quartz substrate. The refractive index changes above the sensor surface, which is due to the appearance of gas or the absorption of biomolecules, can be detected by measuring the resulting spectral shifts of the absorption coefficient. Since the CPA efficiency depends strongly on the number of plasmonic nano-particles and the nano particles location, binary particle swarm optimization (BPSO) algorithm is used to design an optimized array of the plasmonic nano-bi-domes. This optimized structure should be maximizing the absorption coefficient only in the one frequency. BPSO algorithm, a swarm of birds including a matrix with binary entries responsible for controlling nano-bi-domes in the array, shows the presence with symbol of (‘1’) and the absence with (‘0’). The sensor can be used for sensing both gas and low-refractive-index materials in an aqueous environment.